Research on Water Resource Problems of Capital Economic Circle Based on Circular Economy - Jinghua Sha; Nan Xiang; Lin Guo; Runbo Gu (European Regional Science Association (ERSA), 2010)
Capital Economic Circle that is located in north of China belongs to water resources shortage regions. The per capita water of it is only 1/7 of the per capita water of the whole country, and 1/30 of the per capita water of the whole world. Thus water resources problems become one of the key factors that restrict regional development. According to the analysis of water resources situation in Capital Economic Circle, in this paper we find out some main problems existing in regional water resources utilization. These water problems contain a series of water resource problems, such as water environment, water ecology, and water disaster. Finally, based on the theory of circular economy, the proposals on developing recycling economy of water resources are put forward.
Keywords: 330; Capital Economic Circle; Water resources; Circular economy